Pengabdian Kepada Masyakarat Melalui Program Pembuatan Papan Petunjuk Jalan di Desa Kerumut - Wahyu Astuti, Ristina; Akrom, Muhamad; Sanusi, Muhammad; Widia Wati, Via; Husnawati Amini, Titik; Sahrul Kadri, Agus; Umam, Saripul (Universitas Mataram, 2023)
Real Work Lectures (KKN) are a concrete manifestation of students' duties to fulfill life skills with the guidance of lecturers. One of the aims of the KKN program carried out in Kerumut Village is to create street name boards which are an important means of providing information about the location and names of streets in an area. There are no street signs yet, which makes it difficult for outsiders to find locations in the area. KKN STKIP and STEI Hamzar East Lombok students have planned a solution to overcome this problem by making directional signs, especially in Kerumut Village. The method used is direct partner solution, namely making road signs which include 8 signboards, with the size of each board being 50 cm x 30 cm. After completing the plaque making, it was continued with painting which was then continued with the installation of the board which was carried out by students and assisted by the local community. Installation of signboards includes signs for village officials' houses, directional signs to important places as well as signs for RT and RW area boundaries in Kerumut Village. Activities carried out in 4 hamlets, namely Toron hamlet, Gubuk Daya hamlet, Benteng hamlet and Dasan Lendang hamlet, were carried out well with the support and assistance of the village residents. There were no significant obstacles in the process of preparation, implementation and evaluation of activities, it's just that the process took a long time. Making and installing road signs or plaques is a form of participation, coordination and active involvement of students, lecturers and local village residents.